Copper-based powder metallurgy friction material and preparation method and application thereof
By using (ZrmTin) (CxOy) as the friction component in copper-based powder metallurgical friction materials, the problems of poor friction coefficient stability and high wear rate in offshore wind turbines are solved, and higher friction performance and corrosion resistance are achieved, and suitable for high-energy braking conditions.
Patent Information
- Application Number
- CN202311302137.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-09
- Publication Date
- 2025-04-11
AI Technical Summary
The existing copper-based powder metallurgical friction materials are poor in the high-energy load and harsh environment of offshore wind turbines, with poor friction coefficient stability, high wear rate and insufficient corrosion resistance, and cannot fully meet the requirements of offshore wind turbines.
Using (ZrmTin) (CxOy) as the friction component, by mixing ZrO2, TiO2 and graphite powder ball milling and performing pressure-free discharge plasma sintering, carbon oxide solid solution powder with a single phase face-centered cubic structure was prepared, and added to the copper-based powder metallurgy friction material, and copper-based powder metallurgy friction material was prepared by cold pressing and hot press sintering processes.
It improves the mechanical properties, wear resistance, friction coefficient and friction coefficient stability of friction materials, enhances the high-temperature stability and oxidation resistance of the material, reduces the wear rate and friction surface temperature, and is suitable for high-energy braking conditions of offshore wind turbines.
Smart Images

Figure BDA0004484937330000091 
Figure HDA0004484937370000011 
Figure HDA0004484937370000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper-based powder metallurgy friction material preparation, and specifically relates to a copper-based powder metallurgy friction material for offshore wind power generation, and a preparation method and application thereof. Background Art
[0002] Wind energy is an inexhaustible, renewable, clean energy. The friction pair of offshore wind turbines has the characteristics of "three highs" (high speed, high torque, and high pressure) and "one special" (ocean water mist and salt spray corrosion environment). The maximum braking speed of offshore wind turbines reaches 100m / s (the takeoff termination braking speed of Boeing 737 aircraft is 90m / s), the braking torque reaches 30000N·m (the single friction pair of Boeing 737 aircraft is 4000N·m), and the braking pressure is 12MPa (the braking pressure of Boeing 737 aircraft is 9MPa). Therefore, offshore wind turbines have put forward new requirements for friction materials, not only a significant improvement in friction braking function, but also more stringent requirements on the structural strength of friction pair materials, and corrosion resistance to ocean water mist and salt spray.
[0003] Brake pad materials are mainly divided into four categories: resin-based composite materials, powder metallurgy friction materials, carbon / carbon composite materials and ceramic-based friction materials. Among them, the friction coefficient of resin-based composite materials is greatly reduced in a humid environment, and the braking ability is reduced. At the same time, because the resin will decompose at high temperatures, its use temperature generally does not exceed 250°C. Carbon / carbon composite materials have low density (~1.8g / cm 3), excellent mechanical properties, thermal properties, corrosion resistance, etc. However, its friction performance is greatly affected by humidity and temperature. Severe oxidation will occur when it exceeds 400°C, resulting in severe wear, and the friction coefficient will be greatly attenuated in the wet state. Ceramic-based friction materials have the characteristics of low density, high oxidation resistance, stable chemical properties, and mechanical properties are less affected by temperature. They are less sensitive to the environment (wet state) and temperature. Among them, the ceramic-based friction material C / C–SiC has good friction and wear properties at high temperatures (≥1650°C). However, under high energy loads, the C / C–SiC self-matching friction pair still has problems with unstable friction coefficient and high wear rate in the train braking system. Powder metallurgy friction material is a friction material made of metal or alloy as the matrix component, adding appropriate lubricating components (graphite, MoS2, etc.) and friction components (metal oxides, carbides), and evenly mixing and pressing and sintering. Copper-based powder metallurgy friction materials use Cu or modified Cu as the matrix, and usually add elements such as Sn, Zn, Fe and Ni to improve the mechanical strength and anti-attenuation performance of the composite material. It has stable friction and wear performance, strong corrosion resistance and excellent thermal conductivity, low loss to the brake disc, and is easy to form a continuous friction film at the friction interface. It is widely used in high-speed train braking, wind power brake pad materials, etc.
[0004] At present, the traditional friction components in copper-based powder metallurgy friction materials include SiC, SiO2, Al2O3, ZrO2, etc. (patent documents CN105063459A, patent document CN107824783A, patent document CN107760919B, etc.), which have the advantages of high elastic modulus, good wear resistance, good high temperature stability, corrosion resistance and low price, but their wettability with copper is poor, resulting in low interface bonding strength, which makes the reinforced particles easy to fall off due to shear force during friction. In addition, these friction components are highly brittle and easily broken under the action of normal impact force and shear force, resulting in increased wear and reduced friction stability.
[0005] In view of the above problems of traditional friction components, many scholars have carried out modification research. Patent document CN109468487B discloses a tungsten carbide reinforced copper-based powder metallurgy friction material and its preparation method. Since WC has good wettability with copper, WC is used as a friction component. Although the friction coefficient of the material is improved, the stability of the friction coefficient is poor. Patent document CN110923498 B discloses a copper-based powder metallurgy friction material containing metal carbide and metal oxide composite ceramic friction components and its preparation method. Metal carbides (WC and VC) and metal oxides (TiO2, ZrO2 and Al2O3) are used as composite ceramic friction components. The advantages of metal carbides and metal oxides as friction components are complementary to each other to improve the comprehensive friction and wear performance of copper-based powder metallurgy friction materials. However, this material has high requirements for ball milling mixing uniformity. Patent document CN111961912B discloses a copper-based powder metallurgy friction material for high-energy braking, which uses h-BN as one of the lubricating components and is combined with ZrSiO4 to improve the thermal shock resistance of the friction material. At the same time, porous sepiolite is added to absorb the heat generated during braking, reduce the friction surface temperature, and make the braking process smooth.
[0006] It can be seen that although the modification of copper-based powder metallurgy friction materials has made certain progress, for the increasingly severe friction conditions of offshore wind energy, the friction materials must not only have a friction coefficient that meets the use range of about 0.35, taking into account wear resistance and high-temperature stability, but also require a high friction coefficient, low wear rate, high-temperature stability and water mist and salt spray corrosion resistance. The current copper-based powder metallurgy friction materials cannot fully meet these requirements. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a copper-based powder metallurgy friction material and its preparation method and application. The friction material can effectively improve the friction and wear performance of the copper-based powder metallurgy friction material, while ensuring that the wear rate of the brake disc mating material is at a low level, meeting the use requirements of offshore wind turbines.
[0008] The present invention is achieved through the following technical solutions:
[0009] A copper-based powder metallurgy friction material, which comprises, by mass percentage, 55% to 65% copper, 12% to 18% iron, 2% to 5% tin, 5% to 8% graphite, 3% to 6% nitride, and 4% to 10% carbon oxide; the molecular formula of the carbon oxide is (Zr m Ti n )(C x O y ), where 0.7<m≤0.9, 0.1<n≤0.3, 0.6<x≤0.9, 0.4<y≤0.1; (Zr m Tin )(C x O y ) is a quaternary solid solution with a single phase face-centered cubic structure.
[0010] Preferably, the nitride is boron nitride.
[0011] The method for preparing the copper-based powder metallurgy friction material comprises:
[0012] S1, mixing copper powder, iron powder, tin powder, graphite powder, nitride powder and carbon oxide powder;
[0013] S2, cold pressing the raw materials mixed in S1;
[0014] S3, hot pressing and sintering the raw materials formed in S2 under a protective atmosphere to obtain a copper-based powder metallurgy friction material.
[0015] Preferably, in S1, the method for preparing the carbon oxide powder is: ball-milling and mixing ZrO2 powder, TiO2 powder and graphite powder, performing pressureless discharge plasma sintering, crushing and ball-milling to obtain the carbon oxide powder.
[0016] Furthermore, the conditions of the pressureless discharge plasma sintering are: vacuum degree less than 5 Pa, temperature 1500-1800° C., heat preservation 30-120 min, and heating rate 50-150° C. / min.
[0017] Preferably, in S1, the particle size of the copper powder is 60-100 μm, the particle size of the iron powder is 60-100 μm, the particle size of the tin powder is 60-100 μm, the particle size of the graphite is 20-200 μm, the particle size of the nitride is 1-4 μm, and the particle size of the carbon oxide powder is less than 44 μm.
[0018] Preferably, in S2, the cold pressing pressure is 300-600 MPa, and the holding time is 1-30 min.
[0019] Preferably, in S3, the conditions for hot pressing sintering are: hot pressing pressure of 1-3 MPa, sintering temperature of 850-980° C., and heat preservation time of 0.5-3 h.
[0020] A brake friction pair, whose material is the copper-based powder metallurgy friction material.
[0021] An offshore wind power generator set comprises the braking friction pair.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention uses (Zr m Ti n )(Cx O y ) as a friction component, (Zr m Ti n )(C x O y ) is a quaternary solid solution with a carbide face-centered cubic crystal structure and contains oxygen. It has both the wettability of carbide and copper matrix and the toughness and elastic modulus of oxide. It is a carbide solid solution with high temperature stability and high oxidation resistance, high hardness and good wear resistance. m Ti n )(C x O y ) is added to copper-based powder metallurgy friction materials, (Zr m Ti n )(C x O y ) has good wettability with copper and high interface bonding strength with the copper matrix, so it is not easy to fall off during the friction process, effectively improving the mechanical properties, wear resistance, friction coefficient and friction coefficient stability of the friction material, and making up for the shortcomings of poor wettability of oxides (ZrO2, TiO2) with the copper matrix. m Ti n )(C x O y ) has good toughness and elastic modulus, and is not easy to break or fracture under the impact of normal load and shear force, which makes up for the shortcomings of carbide (ZrC, TiC) particles being relatively brittle and having weak impact resistance. m Ti n )(C x O y ) as a friction component, it can combine the wettability of carbides with copper matrix and the toughness and elastic modulus of oxides, thereby improving the comprehensive friction and wear performance of friction materials. The copper-based powder metallurgy friction material of the present invention and the forged steel brake disc do not have cracks and defects during high-energy braking, showing good matching and excellent friction stability, and is suitable for offshore wind power generation.
[0024] The preparation method of the copper-based powder metallurgy friction material of the present invention has simple process, easy operation and easy implementation.
[0025] Furthermore, the present invention uses ZrO2 powder, TiO2 powder and graphite powder as raw materials, through ball milling and pressureless discharge plasma sintering, to successfully prepare (Zr m Ti n )(C x O y )Quaternary solid solution, no other impurities. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the X-ray diffraction spectrum of carbon oxide powder in Example 1;
[0027] Figure 2 This is the X-ray diffraction spectrum of carbon oxide powder of Comparative Example 1. DETAILED DESCRIPTION
[0028] In order to further understand the present invention, the present invention is described below in conjunction with embodiments. These descriptions are only to further explain the features and advantages of the present invention and are not intended to limit the claims of the present invention.
[0029] The copper-based powder metallurgy friction material of the present invention comprises, by mass percentage, 55% to 65% copper, 12% to 18% iron, 2% to 5% tin, 5% to 8% graphite, 3% to 6% nitride, and 4% to 10% carbon oxide; the molecular formula of the carbon oxide is (Zr m Ti n )(C x O y ), where 0.7<m≤0.9, 0.1<n≤0.3, 0.6<x≤0.9, 0.4<y≤0.1; (Zr m Ti n )(C x O y ) is a quaternary solid solution with a single phase face-centered cubic structure.
[0030] The nitride of the present invention is preferably boron nitride.
[0031] The method for preparing the copper-based powder metallurgy friction material of the present invention comprises the following steps:
[0032] S1, weighing and proportioning copper powder, iron powder, tin powder, graphite powder, nitride powder and carbon oxide powder;
[0033] S2, mixing: evenly mix the weighed copper powder, iron powder, tin powder, graphite powder, nitride powder and carbon oxide powder in a V-type mixer for 2 to 8 hours;
[0034] S3, cold pressing: putting the mixed raw materials in S2 into a cold pressing mold for cold pressing, the cold pressing pressure is 300-600 MPa, and the pressure holding time is 1-30 minutes;
[0035] S4, hot pressing and sintering: the raw materials pressed and formed in S3 are placed in a hot pressing and sintering mold, and placed in a vacuum hot pressing and sintering furnace. Argon is used as the protective gas during the sintering process.
[0036] The technical difficulty of the present invention lies in how to prepare (Zr m Ti n )(C x O y) quaternary solid solution powder, which has a face-centered cubic crystal structure of carbide and contains oxygen, and has both the wettability of carbide and copper matrix and the toughness and elastic modulus of oxide.
[0037] In S1 of the present invention, the preparation method of carbon oxide powder is: ZrO2 powder, TiO2 powder and graphite powder are ball-milled and mixed, and after being kept at high temperature by pressureless discharge plasma, the powder is crushed and ball-milled to obtain carbon oxide solid solution powder. The purity of ZrO2 powder, TiO2 powder and graphite powder are all ≥98%, and the particle size is micrometer or nanometer level.
[0038] The ball milling mixing speed is 150-300 rpm, the time is 1-5 hours, the ball milling medium is ethanol and / or water, and the ball-to-material ratio is (6-10):1; the high temperature insulation conditions of the pressureless discharge plasma are: the vacuum degree in the furnace is less than 5 Pa, the temperature is 1500-1800° C., the insulation is 30-120 minutes, and the heating rate is 50-150° C. / min; after the crushing, the ball milling is used to pulverize, the speed is 150-300 rpm, the ball milling time is 1-2 hours, the ball milling medium is ethanol and / or water, and the ball-to-material ratio is (6-10):1. The particle size of the carbon oxide powder after ball milling is less than 44 μm.
[0039] In S1 of the present invention, the copper powder is electrolytic copper powder (particle size is 60-100 μm), the iron powder is reduced iron powder (particle size is 60-100 μm), the tin powder is atomized tin powder (particle size is 60-100 μm), the graphite is natural flaky graphite (particle size is 20-200 μm), and the nitride is hexagonal nitride (particle size is 1-4 μm). The particle size of the carbon oxide powder is less than 44 μm, preferably 10-20 μm.
[0040] In S4 of the present invention, the hot pressing pressure is 1-3 MPa, the pressing time is 1-6 h, the sintering temperature is 850-980° C., the heating time is 0.5-3 h, and the heat preservation time is 0.5-3 h.
[0041] In S4 of the present invention, the sintering density of the copper-based powder metallurgy friction material is 4.6 to 5.2 g / cm 3 The friction coefficient of the obtained copper-based powder metallurgy friction material is 0.31-0.38, and the wear loss when paired with forged steel is 0.28-0.33 cm 3 / MJ.
[0042] Embodiment 1:
[0043] Preparation of copper-based powder metallurgy friction material: First, prepare a mixture, the raw materials of which include: 60% copper powder, 15% iron powder, 5% tin powder, 6% graphite powder, 6% boron nitride powder, and 8% carbon oxide powder. Mix the mixture in a V-type mixer for 5 hours, and make a compact under a pressing pressure of 500MPa. Place the compact in a vacuum hot pressing sintering furnace for sintering, the sintering temperature is 950℃, the holding time is 3h, the sintering pressure is 3MPa, and the sintering atmosphere is argon. After the insulation is completed, the unit pressure of 2MPa is still maintained, and the furnace is first cooled to below 800℃, and then the heating furnace body is removed, air-cooled to below 600℃, and finally water-cooled to below 80℃ before being taken out of the furnace.
[0044] The preparation method of carbon oxide powder is as follows: ZrO2 powder, TiO2 powder and graphite powder are ball-milled for 2 hours in a planetary ball mill according to a molar ratio of 0.8:0.2:2.2, wherein the particle size of ZrO2 powder and TiO2 powder is -300 mesh, the graphite powder is -4000 mesh, the purity is ≥99%, the ball milling medium is ethanol, the rotation speed is 150rpm, the ball-to-material ratio is 6:1, and after ball milling, the mixture is taken out and dried at 40°C, and the mixed powder is obtained after sieving. The mixed powder is placed in a pressureless discharge plasma sintering graphite mold for pressureless discharge plasma sintering, the vacuum degree in the furnace is less than 5Pa, the temperature is raised to 1700°C and kept for 30 minutes, the heating rate is 100°C / min, and then cooled to room temperature, taken out and broken, and ball-milled into powder in a ball mill, the ball milling time is 2 hours, the ball milling medium is ethanol, the rotation speed is 200rpm, the ball-to-material ratio is 6:1, and the carbon oxide powder is obtained after drying at 40°C, and the particle size is about 20μm. The prepared carbon oxide has a single phase (such as Figure 1 The four elements Zr, Ti, C, and O are evenly distributed among each other. According to the ICP-OES element content test and analysis, the atomic ratio of Zr and Ti is 0.8:0.2, and the atomic ratio of C and O is 0.6:0.4, forming (Zr 0.8 Ti 0.2 )(C 0.6 O 0.4 ) solid solution.
[0045] Embodiment 2:
[0046] Preparation of copper-based powder metallurgy friction material: First, prepare a mixture, the raw materials of which include: 55% copper powder, 15% iron powder, 7% tin powder, 8% graphite powder, 6% boron nitride powder, and 9% carbon oxide powder. Mix the mixture in a V-type mixer for 8 hours, and make a compact under a pressing pressure of 600MPa. Place the compact in a vacuum hot pressing sintering furnace for sintering, the sintering temperature is 950℃, the holding time is 3h, the sintering pressure is 3MPa, and the sintering atmosphere is argon. After the insulation is completed, the unit pressure of 2MPa is still maintained, and the furnace is first cooled to below 800℃, and then the heating furnace body is removed, air-cooled to below 600℃, and finally water-cooled to below 80℃ before being taken out of the furnace.
[0047] The preparation method of carbon oxide powder is as follows: ZrO2 powder, TiO2 powder and graphite powder are ball-milled for 3 hours in a planetary ball mill according to a molar ratio of 0.7:0.3:2.4, wherein the particle size of ZrO2 powder and TiO2 powder is -300 mesh, the graphite powder is -4000 mesh, the purity is ≥99%, the ball milling medium is ethanol, the rotation speed is 150rpm, the ball-to-material ratio is 6:1, and after ball milling, the mixture is taken out and dried at 40°C, and the mixed powder is obtained after sieving. The mixed powder is placed in a pressureless discharge plasma sintering graphite mold for pressureless discharge plasma sintering, the vacuum degree in the furnace is less than 5Pa, the temperature is raised to 1600°C and kept for 60min, the heating rate is 100°C / min, and then cooled to room temperature, taken out and broken, and ball-milled into powder in a ball mill, the ball milling time is 2h, the ball milling medium is ethanol, the rotation speed is 200rpm, the ball-to-material ratio is 6:1, and the carbon oxide powder is obtained after drying at 40°C, and the particle size is about 20μm. The four elements of Zr, Ti, C, and O in the prepared carbon oxide are evenly distributed. The atomic ratio of Zr to Ti is 0.7:0.3, and the atomic ratio of C to O is 0.7:0.3, forming (Zr 0.7 Ti 0.3 )(C 0.7 O 0.3 ) solid solution.
[0048] Embodiment 3:
[0049] Preparation of copper-based powder metallurgy friction material: First, prepare a mixture, the raw materials of which include: 65% copper powder, 12% iron powder, 4% tin powder, 6% graphite powder, 3% boron nitride powder, and 10% carbon oxide powder. Mix the mixture in a V-type mixer for 5 hours, and make a compact under a pressing pressure of 600MPa. Place the compact in a vacuum hot pressing sintering furnace for sintering, the sintering temperature is 950℃, the holding time is 3h, the sintering pressure is 3MPa, and the sintering atmosphere is argon. After the insulation is completed, the unit pressure of 2MPa is still maintained, and the furnace is first cooled to below 800℃, and then the heating furnace body is removed, air-cooled to below 600℃, and finally water-cooled to below 80℃ before being taken out of the furnace.
[0050] The preparation method of carbon oxide powder is as follows: ZrO2 powder, TiO2 powder and graphite powder are ball-milled for 3 hours in a planetary ball mill according to a molar ratio of 0.9:0.1:2.4, wherein the particle size of ZrO2 powder and TiO2 powder is -300 mesh, the graphite powder is -4000 mesh, the purity is ≥99%, the ball milling medium is ethanol, the rotation speed is 150rpm, the ball-to-material ratio is 6:1, and after ball milling, the mixture is taken out and dried at 40°C, and the mixed powder is obtained after sieving. The mixed powder is placed in a pressureless discharge plasma sintering graphite mold for pressureless discharge plasma sintering, the vacuum degree in the furnace is less than 5Pa, the temperature is raised to 1500°C and kept for 120min, the heating rate is 100°C / min, and then cooled to room temperature, taken out and broken, and ball-milled into powder in a ball mill, the ball milling time is 2h, the ball milling medium is ethanol, the rotation speed is 200rpm, the ball-to-material ratio is 6:1, and the carbon oxide powder is obtained after drying at 40°C, and the particle size is about 10μm. The four elements of Zr, Ti, C, and O in the prepared carbon oxide are evenly distributed. The atomic ratio of Zr to Ti is 0.9:0.1, and the atomic ratio of C to O is 0.7:0.3, forming (Zr 0.9 Ti 0.1 )(C 0.7 O 0.3 ) solid solution.
[0051] Comparative Example 1:
[0052] Preparation of copper-based powder metallurgy friction material: First, prepare a mixture, the raw materials of which include: 60% copper powder, 15% iron powder, 5% tin powder, 6% graphite powder, 6% boron nitride powder, and 8% carbon oxide powder. Mix the mixture in a V-type mixer for 5 hours, and make a compact under a pressing pressure of 500MPa. Place the compact in a vacuum hot pressing sintering furnace for sintering, the sintering temperature is 950℃, the holding time is 3h, the sintering pressure is 3MPa, and the sintering atmosphere is argon. After the insulation is completed, the unit pressure of 2MPa is still maintained, and the furnace is first cooled to below 800℃, and then the heating furnace body is removed, air-cooled to below 600℃, and finally water-cooled to below 80℃ before being taken out of the furnace.
[0053] The preparation method of carbon oxide powder is as follows: Zr powder, Ti powder and graphite powder are ball-milled for 2 hours in a planetary ball mill according to a molar ratio of 0.8:0.2:0.6, wherein the particle size of Zr powder and Ti powder is -300 mesh, the graphite powder is -4000 mesh, the purity is ≥99%, the ball milling medium is ethanol, the rotation speed is 150rpm, the ball-to-material ratio is 6:1, and after ball milling, it is taken out and dried at 40°C, and then sieved to obtain a mixed powder. The mixed powder is placed in a pressureless discharge plasma sintering graphite mold for pressureless discharge plasma sintering, the vacuum degree in the furnace is less than 5Pa, the temperature is raised to 1700°C and kept for 30 minutes, the heating rate is 100°C / min, and then cooled to room temperature, taken out and broken, and ball-milled into powder in a ball mill, the ball milling time is 2 hours, the ball milling medium is ethanol, the rotation speed is 200rpm, the ball-to-material ratio is 6:1, and the carbide solid solution powder is obtained after drying at 40°C. The carbide powder was then kept in air at 600°C for 1 h to obtain oxidized powder.
[0054] like Figure 2 As shown in the figure, the diffraction peaks of Zr-Ti-CO solid solution phase and t-(Zr,Ti)O2 appear in the prepared powder, indicating that the powder is a mixture of these two substances. Therefore, it is shown that the carbide solid solution is synthesized first and then oxidized, and a single phase of carbon oxide powder cannot be prepared. When the added carbon oxide powder is a mixed multiphase compound, the average friction coefficient and wear amount of the friction material obtained will increase, and the comprehensive friction and wear performance will decrease (see Table 1).
[0055] The above embodiments and comparative example 1 were subjected to friction and wear tests on an MM-3000 test machine. The MM-3000 scaled test machine was used. The product friction surface size was 20×15 mm, the mating piece was forged steel, and the braking energy density was 4200 J / cm 2 The braking times are 10 times, and the test results are shown in Table 1. The product of the embodiment of the present invention can achieve braking when paired with forged steel under high-energy braking conditions without cracks or defects.
[0056] Table 1 Friction and wear properties of materials in Examples and Comparative Examples
[0057]
[0058] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A copper-based powder metallurgy friction material, characterized in that: The components include, by mass percentage, 55% to 65% copper, 12% to 18% iron, 2% to 5% tin, 5% to 8% graphite, 3% to 6% nitride, and 4% to 10% carbon oxide; the molecular formula of the carbon oxide is (Zr m Ti n )(C x O y ), where 0.7<m≤0.9, 0.1<n≤0.3, 0.6<x≤0.9, 0.4<y≤0.1; (Zr m Ti n )(C x O y ) is a quaternary solid solution with a single phase face-centered cubic structure.
2. The copper-based powder metallurgy friction material according to claim 1, characterized in that: The nitride is boron nitride.
3. The method for preparing the copper-based powder metallurgy friction material according to any one of claims 1 to 2, characterized in that: include: S1, mixing copper powder, iron powder, tin powder, graphite powder, nitride powder and carbon oxide powder; S2, cold pressing the raw materials mixed in S1; S3, hot pressing and sintering the raw materials formed in S2 under a protective atmosphere to obtain a copper-based powder metallurgy friction material.
4. The method for preparing a copper-based powder metallurgy friction material according to claim 3, characterized in that: In S1, the method for preparing the carbon oxide powder is: ball-milling and mixing ZrO2 powder, TiO2 powder and graphite powder, performing pressureless discharge plasma sintering, crushing and ball-milling to obtain the carbon oxide powder.
5. The method for preparing a copper-based powder metallurgy friction material according to claim 4, characterized in that: The conditions of the pressureless discharge plasma sintering are: vacuum degree less than 5 Pa, temperature 1500-1800° C., heat preservation 30-120 min, and heating rate 50-150° C. / min.
6. The method for preparing a copper-based powder metallurgy friction material according to claim 3, characterized in that: In S1, the particle size of the copper powder is 60-100 μm, the particle size of the iron powder is 60-100 μm, the particle size of the tin powder is 60-100 μm, the particle size of the graphite is 20-200 μm, the particle size of the nitride is 1-4 μm, and the particle size of the carbon oxide powder is less than 44 μm.
7. The method for preparing a copper-based powder metallurgy friction material according to claim 3, characterized in that: In S2, the cold pressing pressure is 300-600 MPa, and the holding time is 1-30 min.
8. The method for preparing a copper-based powder metallurgy friction material according to claim 3, characterized in that: In S3, the hot pressing sintering conditions are: hot pressing pressure of 1-3 MPa, sintering temperature of 850-980° C., and heat preservation time of 0.5-3 h.
9. A brake friction pair, characterized in that: The material thereof is the copper-based powder metallurgy friction material described in any one of items 1 to 2.
10. An offshore wind turbine generator set, characterized in that: Includes the brake friction pair as described in claim 9.
Citation Information
Patent Citations
Copper-based powder metallurgy friction material for high-speed train braking and preparation method thereof
CN105063459A
A method for preparing high-temperature resistant copper-based metallurgical friction materials
CN107760919B
Copper-iron based powder metallurgy friction material for high-speed train braking and preparation method
CN107824783A
A tungsten carbide-reinforced copper-based powder metallurgy friction material and its preparation method
CN109468487B
A copper-based powder metallurgy friction material containing composite ceramic friction components of metal carbides and metal oxides and its preparation method.
CN110923498B